Risk factors and a prediction model for unruptured intracranial aneurysms in patients with ischemic stroke using carotid intima-media thickness and systemic atherosclerosis - Gao, Gaiming; Kang, Dezhi; Zhang, Jinning; Jiang, Zhixian; He, Xueyang; Wu, Yanyu (Frontiers in Neurology, 2023)
Background: Systemic atherosclerosis and carotid intima-media thickness (IMT) have been widely used in clinical practice for ischemic stroke; however, little is known about the risk factors for unruptured intracranial aneurysms (UIA) in patients with ischemic stroke (IS). Therefore, we performed this study to identify the risk factors and construct a prediction model for UIA in patients with IS.: Data were retrospectively collected on patients with IS from 2015 to 2022 at The First Hospital of Quanzhou City. Risk factors for UIA in patients with IS were identified using a multivariate logistic regression model, and a receiver operating characteristic (ROC) curve was applied to construct the prediction model. Results: Out of the 122 patients with IS, 52 presented with UIA (ISUIA) in study group, and the remaining 70 patients without UIA (IS) in control group. Patients in the ISUIA group had lower carotid IMT and carotid artery plaque scores than those in the IS group (P<0.05). Multivariate analyses found that aspirin use (OR:12.987; P=0.031), elevated C-reactive protein (CRP) level (OR:1.019; P=0.004), and carotid IMT > 0.09 mm (OR:0.218; P<0.001) were significantly associated with the risk of UIA in patients with IS. However, UIA in patients with IS was unaffected by the carotid artery plaque score (P=0.114). The constricted prediction model based on the abovementioned factors for UIA in IS patients was 0.79 (95% CI:0.71-0.87).The findings revealed that the risk factors for UIA in patients with IS included aspirin use, elevated CRP level, and smaller carotid IMT, and the predictive value of the prediction model was relatively better.